2009
DOI: 10.1097/aud.0b013e31819c3ea0
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Acoustic Stapedial Reflex Test in Healthy Neonates

Abstract: This study demonstrated that ASRs could be consistently elicited from healthy neonates who showed a single-peaked configuration in the high-frequency tympanometry test and passed the automated auditory brain stem response and TEOAE tests. The findings showed that the ASRTs did not vary significantly across the test-retest conditions, and the high intracorrelation coefficients illustrate the reliability of the ASR test. Given the high test-retest reliability, the ASR test holds promise as a useful diagnostic/sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
5
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 43 publications
4
38
5
2
Order By: Relevance
“…The resulting application to adult ears with a BBN activator showed lower ASRTs than in clinical tests. The ASR procedures for neonatal ears used a range of reference frequencies from 0.8 to 2.8 kHz, which overlapped and extended the 1-kHz reference frequency that Mazlan et al (2009) used to detect ASR shifts in neonatal ears.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting application to adult ears with a BBN activator showed lower ASRTs than in clinical tests. The ASR procedures for neonatal ears used a range of reference frequencies from 0.8 to 2.8 kHz, which overlapped and extended the 1-kHz reference frequency that Mazlan et al (2009) used to detect ASR shifts in neonatal ears.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of acoustic reflex at 50, 55, or 60 dB was higher with the 1,000 Hz probe. Lower ASRTs were also found (10,21,22) and were justified by the small size of the external auditory canal of newborns by vibration of the wall of the canal after a sound stimulus. However, it is worth to mention that the minimum intensity for the analysis of AR in the equipment is 50 dB NPS.…”
Section: Discussionmentioning
confidence: 93%
“…With the 1,000 Hz probe, the average was 74.2 dB for the 1,000 Hz frequency and 62.9 dB for 2,000 Hz (Table 1). A study (21) found a mean of 93 dB for the 1,000 Hz and two other studies (10,22) found means of 73.05 and 76.2 dB for 1,000 and 2,000 Hz, respectively. In the these studies, no other frequencies were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations